Smith-Purcell radiation from periodic beams - Sergeeva D. Yu. Darjya Yurjevna; Potylitsyn A. P. Alexander Petrovich; Tishchenko A. A. Aleksey Aleksandrovich; Strikhanov M. N. Mikhail Nikolaevich (2017, 2017)
Title screen